The role of professional socialisation in confidence in vaccines and vaccination decision-makers: Insights from a large multi-wave survey in France - Hugo Touzet; Sophie Privault; Jeremy K. Ward (PLoS ONE, 2025)
The Covid-19 pandemic has greatly expanded research on social determinants of health inequalities. Yet one crucial dimension remains underexplored: the influence of professional socialisation (i.e., the process through which individuals acquire not only knowledge and skills, but also a worldview and a culture associated with the profession they practice). This gap is striking given the extensive sociological evidence that professional identities profoundly shape individuals’ life paths, perceptions, and health experiences. In this article, we take advantage of a very large multi-wave survey conducted in France during the Covid-19 pandemic (n > 100,000) to explore in greater depth the relationship between occupation and attitudes to vaccination and to stakeholders involved in vaccination policymaking. We show that, controlling for various socio-demographic factors, major disparities emerge, not only between broad professional groups at different places in the social hierarchy, but also between professions with comparable situations in this hierarchy. For instance, we show that public sector employees are more in favour of vaccinations but less confident in the government than their private sector counterparts. To understand these differences, we draw on the sociology of the relationship between professional socialisations and ordinary relationships to politics and the State.